Peran Model Pembelajaran Futuristik dalam Kemajuan PAI di Pondok Pesantren - Budiyono, Slamet; Adin, Ahmad Muchlis (Lembaga Yasin AlSys, 2024)
The concept of futuristic learning in the education sector is very important to produce Indonesian human resource products that can face the changing times. This requires educational institutions and educators to be able to create futuristic learning concepts which are expected to meet the needs of the educational process, especially Islamic religious education in this era. Among the most common Islamic religious educational institutions in Indonesia are Islamic boarding schools, some of which still use traditional methods. Combining futuristic learning models with traditional methods can create a dynamic and effective learning environment to advance Islamic religious education in Islamic boarding schools.